2019
DOI: 10.1111/soin.12329
|View full text |Cite
|
Sign up to set email alerts
|

“Welcome! Oh, wait…” Transgender Military Service in a Time of Uncertainty

Abstract: In 2014, the Department of Defense began a broad review of transgender military service. Following this review, in 2016, the Obama Administration announced a policy of transgender inclusion in the military. However, in 2017, before enactment of that policy, President Trump announced the reinstatement of a ban on transgender military service. Although, in the last five years, these events have garnered much media attention, sociologists have generally left them unexplored. In this article, I begin the process o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…For example, transgender veterans are likely to have experienced military sexual trauma, 42 and exposure to former and current Department of Defense policies barring transgender soldiers from openly serving in the military are unique stressors. 43,44 Additionally, transgender veterans who receive VA healthcare may have different experiences than those who do not, as trauma and discrimination experienced during military service may prevent some transgender veterans from seeking VA care. 45 This study may therefore be limited in generalizability to VA patients; however, we observed similar prevalence of drug use disorders among transgender VA patients compared to a prior study of transgender patients in non-VA U.S. healthcare systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, transgender veterans are likely to have experienced military sexual trauma, 42 and exposure to former and current Department of Defense policies barring transgender soldiers from openly serving in the military are unique stressors. 43,44 Additionally, transgender veterans who receive VA healthcare may have different experiences than those who do not, as trauma and discrimination experienced during military service may prevent some transgender veterans from seeking VA care. 45 This study may therefore be limited in generalizability to VA patients; however, we observed similar prevalence of drug use disorders among transgender VA patients compared to a prior study of transgender patients in non-VA U.S. healthcare systems.…”
Section: Discussionmentioning
confidence: 99%
“…When interpreting these findings, it is important to consider how lived experiences of transgender veterans may differ from transgender nonveterans in ways that may impact gender minority stress and subsequent risk of drug use disorders. For example, transgender veterans are likely to have experienced military sexual trauma, 42 and exposure to former and current Department of Defense policies barring transgender soldiers from openly serving in the military are unique stressors 43,44 . Additionally, transgender veterans who receive VA healthcare may have different experiences than those who do not, as trauma and discrimination experienced during military service may prevent some transgender veterans from seeking VA care 45 .…”
Section: Discussionmentioning
confidence: 99%
“…My conceptualization of gender status is more similar to what Ashley (2021) calls “gender modality;” however, I use the term “status” because I am analytically interested in the “comparative social ranking” (Ridgeway 2019:1) between cisness and non‐cisness. “Gender status” is also a nod to multidisciplinary works that increasingly use the term “transgender status” in discussing the life chances and social experiences of non‐cis people (Bowers and Whitley 2020; Carpenter et al 2020; Doan 2016; Embser‐Herbert 2020; Schilt and Lagos 2017).…”
Section: What Are Gender Category and Gender Status?mentioning
confidence: 99%